A comparative study of disinfecting catheter caps and their effectiveness in the reduction of equine IV catheter-related thrombophlebitis. Issue 3 (4th March 2018) - Fisk, Natalie
Abstract: The aim of this study was to identify whether the use of disinfecting catheter caps reduced the incidence of catheter-related thrombophlebitis in equine patients. Also of interest was if they minimised the long-term incidence of thrombophlebitis in equine patients with indwelling intravenous over-the-wire catheters. This was a retrospective pilot study, which involved 40 equine patients from 2012 and 40 equine patients from 2013. The results of the study showed a reduction in the number of patients that suffered from thrombophlebitis in the year 2013. The p -value (calculated probability) test for difference was 0.071; due to the number being larger than 0.05, this indicated there was a borderline significance and that the study could have been slightly underpowered. This led to the conclusion that disinfecting catheter caps reduced the rate of thrombophlebitis in the intravenously catheterised horse, thus supporting the researcher's hypothesis.